(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVES: The antiplaque and antigingivitis effect of Lippia Sidoides (LS) was evaluated in this in vivo investigation. MATERIAL AND METHODS: Twenty-three subjects participated in a cross-over, double-blind clinical study, using 21-day partial-mouth experimental model of gingivitis. A toothshield was constructed for each volunteer, avoiding the brushing of the 4 experimental posterior teeth in the lower left quadrant. The subjects were randomly assigned initially to use either the placebo gel (control group) or the test gel, containing 10% LS (test group). RESULTS: The clinical results showed statistically significant differences for plaque index (PLI) (p